Implentasi Motode Manhaji Dalam Memahami Kitab Kuning Di Pondok Pesantren Darul Arifin Jambi - Rido Noviansyah; Muhammad Fadhil; Abdullah Firdaus (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Implementation of the Manhaji Method in understanding the yellow book at the Darul Arifin Muaro Islamic Boarding School, Jambi, Islamic Religious Education Master's Study Program, Sulthan Tthaha Saifuddin University, Jambi 2024.Methods for understanding the Yellow Book in learning activities, especially in the method of reading yellow words, educators must try to achieve the goals as much as possible. One way is to use appropriate teaching methods. Method is one of the tools to achieve learning goals. Therefore, educators should be smart in choosing and using the right methods so that they can support teaching and learning activities and can be used as efficient tools to achieve goals. The purpose of this research is to describe (1) To find out the background and purpose of implementing the Manhaji method in learning the Yellow Book for students at the Darul Arifin Islamic boarding school. (2) To find out the obstacles in the field to the application of the Manhaji method at the Darul Arifin Islamic boarding school. (3) To find out the application of the Manhaji method at the Darul Arifin Islamic boarding school. This research was conducted at Darul Arifin Muaro Jambi using qualitative research and a descriptive approach. Research data collection techniques use interviews, observation and documentation. Data analysis for this research was carried out using the steps of data collection, data reduction, drawing conclusions and verification. Meanwhile, diligent observation and triangulation as well as discussions were carried out as an effort to test the validity of the data. The results of this research show that: (1) The Manhaji learning concept is divided into several parts, starting from planning objectives, determining learning materials, determining methods, determining time allocation and use of media. (2) The implementation carried out during learning in madrasa classes is divided into three parts, namely preliminary activities, core learning activities, and closing activities. (3) Manhaji content/material, as follows: volume I (Mastering the ins and outs of Isim and fi'il which include, ma'rifat nakirah, Mabni, Mu'rob, Tasrif Fi'il patterns) volume II (Mastering the Tasrif Fi'il patterns il Mazid, and Mustaqqaat such as isim Fail. Maful, isim Zaman and Isim Makan), volume III (Mastering Umdah Sum, Mubtada, Khabar, Fi'il Fail, and Awamil. (Inna, Kaana and Dhzanna) volume IV (Mastering Takmilah Sum (Na'at taukid, Athf Badal Mafu'lat). (4) Evaluation of Manhaji material is carried out during the learning process and outside the learning process, in the form of written tests and oral tests.